Identification of coxsackievirus A24 variant during an acute hemorrhagic conjunctivitis outbreak in coastal Kenya, 2024 [version 2; peer review: 1 approved, 3 approved with reservations] - Salim Mwarumba; Arnold W. Lambisia; Joseph Mwangangi; Fredrick K.N. Korir; John Mwita Morobe; Rebecca Kiptui; Raila Seif Athman; Nelly Mugo; Micheal Mbee; Lynette Isabella Ochola-Oyier; Charlotte J. Houldcroft; Penny Muange; et al. (Wellcome Open Research)
Background In early 2024, a surge in acute hemorrhagic conjunctivitis (AHC), also referred as “red eye” disease, was observed in coastal Kenya, prompting the Ministry of Health to issue an outbreak alert. Herein, we investigated the etiology of this outbreak. Methods Ocular swabs were obtained from 13 individuals presenting with AHC at a Mombasa clinic in early February 2024. Ten of these were analyzed using bacterial cultures, and all 13 using a pan-adenovirus quantitative PCR (qPCR) and metagenomic sequencing. Potential viral etiology was confirmed by a specific qPCR, amplicon sequencing and phylogenetic analysis. Results Bacterial cultures yielded no growth except in three samples where non-pathogenic bacteria were detected. All 13 samples were adenovirus qPCR negative. Metagenomic sequencing detected coxsackievirus A24 variant (CA24v) in three of the 13 samples. CV-A24v detections were confirmed by both CV-A24v specific qPCR and amplicon sequencing of an approximately 450 nucleotide long VP4/2 junction genomic region. Phylogenetic analysis of the VP4/2 sequences showed that they were closely related to CV-A24v genotype IV. Conclusion The AHC epidemic in coastal Kenya in early 2024 was likely caused by CA24v. Metagenomic sequencing is a powerful tool for identifying potential causative agents of new disease outbreaks.